0721 Daytime Sleepiness and Napping in Nursing-Home Eligible Community Dwelling Older Adults: A Mixed Methods Study. (27th April 2018) - McPhillips, M V; Li, J; Cacchione, P Z; Dickson, V V; Gooneratne, N S; Riegel, B J
Abstract: Introduction: Estimates of daytime sleepiness in community dwelling older adults range from 10–30% and reach 70% in nursing home residents. Daytime napping is also common in older adults. The aim of this study was to describe daytime sleepiness and napping in nursing-home eligible community dwelling older adults. Methods: We conducted a concurrent nested mixed method study. A purposive sample of 40 older adults (aged ≥55) was recruited from one urban Program of All-Inclusive Care for Elders. We obtained qualitative data via semi-structured interviews. Actigraphy and sleep diary were used to determine daytime napping and Epworth Sleepiness Scale (ESS) was the subjective measure of daytime sleepiness. We defined an intentional nap to be more than 10 minutes in duration; anything less was considered an unintentional nap (i.e., dozing or nodding off). Results: Our final sample (n=40) was primarily female (85%), Black (100%), older adults with a mean age of 72 ± 9.5 years. Most (75%) did not report daytime sleepiness (ESS scores 7.65 ± 5.36). The average duration of total napping per day was 162.80 ± 83.22 minutes with a mean nap frequency per day of 33.95 ± 15.05 naps. The average duration of intentional napping per day was 33.15 ± 11.51 minutes with an intentional nap frequency per day of 2.5 ± 1.47 naps. Intentional napping accounted for roughly 20% of total napping. During the qualitative interviews, of the 35 participants who discussed naps, 75% reported napping daily or occasionally and 25% reported that they do not take naps. Beliefs about napping varied such that some believed a nap was beneficial while others believed napping would negatively affect their nighttime sleep. Conclusion: Our sample napped frequently throughout the day; nap episodes were fragmented. These at-risk older adults did not always recognize that they napped and most reported no daytime sleepiness. Further research is necessary to explore appropriate timing, frequency and duration of naps, intention to nap, and effects of napping over time. Support (If Any): T32NR009356, T32HL07953, Frank Morgan Jones, Tyson, Sigma Theta Tau Funding.